Achievement Motivation of Organic Farmers of Birbhum District of West Bengal - Bhattacharjee, Udayan; Saha, Anindita; Tiwari, Pravin Kumar; Dhakre, Digvijay Singh; Gupta, Ravi Kumar (Indian Journal of Extension Education, 2025)
The study was conducted in 2018 to know the achievement motivation of farmers practicing organic farming in the Birbhum district of West Bengal. The results of the study found a majority of the respondents falling under a medium level of socioeconomic status and achievement motivation. Among the ten independent variables, seven variables were having a positive and highly significant relationship with the dependent variable. Regression analysis shown that all the 10 independent variables put together influenced significant variation in achievement motivation to the extent of R2 45.5 per cent and out of ten variables, only one variable was having positive significance at one percent level of confidence. Path analysis showed that the independent variable affected (direct and indirect effect) on the achievement motivation of farmers practicing organic farming. Sustainable organic farming activity holds significant importance in increasing the profit of crop cultivation in the study area